Application of a Block Copolymer Solution to Ice-Prone Structures - Hanamoto,B. (1983)
The formation of ice on structures causes both operational and structural problems, and much effort must be expended in keeping the systems comprising these structures functional. Preventing ice formation is the ideal solution, but this is usually impossible or cost-prohibitive. An alternative is to make it easier to remove the ice once it forms. Providing a surface that will cause the adhesive bond between the ice and the surface to be weak is a passive means of doing this. Heat or mechanical systems would be active means. The U.S. Army Cold Regions Research and Engineering Laboratory, together with H.H.G. Jellinek of Clarkson College, worked on developing a coating with reduced adhesive strength properties between the ice and the coated surface so that ice removal could be facilitated. A long chain, block copolymer was selected after many compounds with the desired properties had been tested. This article is from 'Proceedings of International Workshop on Atmospheric Icing of Structures (1st) Held at Hanover, New Hampshire on 1-3 June 1982,' AD-A131 869. p155-158.